Corporate Management Reviewed from Financial Performance Viewed from Corporate Social Responsibility - Eko Meiningsih Susilowati (Yayasan Ilomata, 2021)
ABSTRACT This research aims to examine the financial performance viewed from corporate social responsibility in manufacturing companies enlisted in Indonesian Stock Exchange in 2017. The population of research consisted of manufacturing companies enlisted in Indonesian Stock Exchange. The sample employed was manufacturing companies enlisted in Indonesian Stock Exchange in 2017. The sampling technique used was purposive sampling one. Data analysis was conducted using a multiple linear regression. The result of research showed that media exposure and firm size affect positively and significantly the disclosure of corporate social responsibility. Meanwhile, leverage and profitability affect positively but insignificantly the disclosure of corporate social responsibility in manufacturing companies. The result of adjusted R2 test in this research showed value of 0.297. It means that the disclosure of corporate social responsibility is affected by media exposure variable, firm size, leverage and profitability by 29.7%, while the rest of 79.3% was affected by other factors excluded from this study. Keywords: financial performance, corporate social responsibility